2012
DOI: 10.1007/s11517-012-0947-z
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and nonlinear dynamic analysis in patients with stress-induced cardiomyopathy

Abstract: Complexity-based analyses may quantify abnormalities in heart rate variability (HRV). The aim of this study was to investigate the clinical and prognostic significances of dynamic HRV changes in patients with stress-induced cardiomyopathy Takotsubo syndrome (TS) by means of linear and nonlinear analysis. Patients with TS were included in study after complete noninvasive and invasive cardiovascular diagnostic evaluation and compared to an age and gender matched control group of healthy subjects. Series of R-R i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…Twenty-five female patients (60.2 ± 8.3 years) with symptoms and signs of stress-induced cardiomyopathy, were identified and included in the study and the control group consisted of 50 randomly selected age-matched (mean age 63.1 ± 7.2 years) healthy women. The values found for alpha1 and alpha2 were 1.11 ± 0.05 and 1.18 ± 0.04 for the control group and 1.31 ± 0.06 and 1.25 ± 0.05 for the group with cardiomyopathy showing a fractal behavior in the controls and a trend to strongly correlated behavior in the study group [19] . What one finds is that regardless of the studied disease or age, and even sample size and acquisition methodology, values that deviate from the normal value of 1.0 (increasing or decreasing) are associated with higher morbid gravity or worse prognosis revealing loss of fractal behavior toward random or strongly correlated behavior.…”
Section: A Dfa(α)mentioning
confidence: 76%
See 2 more Smart Citations
“…Twenty-five female patients (60.2 ± 8.3 years) with symptoms and signs of stress-induced cardiomyopathy, were identified and included in the study and the control group consisted of 50 randomly selected age-matched (mean age 63.1 ± 7.2 years) healthy women. The values found for alpha1 and alpha2 were 1.11 ± 0.05 and 1.18 ± 0.04 for the control group and 1.31 ± 0.06 and 1.25 ± 0.05 for the group with cardiomyopathy showing a fractal behavior in the controls and a trend to strongly correlated behavior in the study group [19] . What one finds is that regardless of the studied disease or age, and even sample size and acquisition methodology, values that deviate from the normal value of 1.0 (increasing or decreasing) are associated with higher morbid gravity or worse prognosis revealing loss of fractal behavior toward random or strongly correlated behavior.…”
Section: A Dfa(α)mentioning
confidence: 76%
“…These values were 0.98 ± 0.31 and 0.76 ± 0.43 for alfa1 with 1.01 ± 0.09 and 0.99 ± 0.18 for alpha2, respectively. Krstacic G et al (2012) tested the applicability of nonlinear methods for HRV performance evaluation in patients with stressinduced cardiomyopathy (Takotsubo Syndrome or "Broken Heart Syndrome") whose pathogenesis is possibly related to acute release of large amounts of stress hormones leading to effect known as 'catecholamine induced myocardial stunning'. Twenty-five female patients (60.2 ± 8.3 years) with symptoms and signs of stress-induced cardiomyopathy, were identified and included in the study and the control group consisted of 50 randomly selected age-matched (mean age 63.1 ± 7.2 years) healthy women.…”
Section: A Dfa(α)mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of HRV has been used to assess autonomic function. It is altered in many diseases [8][9][10][11] . Th e parameters of HRV have been studied in patients with SCI and calculated from 24-hour Holter electrocardiogram (ECG) 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Sisto et al [24] reported a neonatal pain detector using an acoustic analysis algorithm of crying to provide an objective estimate of neonatal pain. The heart rate itself was further studied by applying mathematical tools such as the heart rate variability (HRV) and other spectral analysis methods (SAM) like the Fourier transform [3,4,16,20]. Extensive studies on adult and pediatric populations using SAM have not managed to produce a reliable, real-time pain detector [17,21,25].…”
Section: Introductionmentioning
confidence: 99%